Analytical Methods for the Determination of Chlorhexidine: A Review - Masquio Fiorentino, Flavia Angelica [UNESP]; Correa, Marcos Antonio [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Taylor & Francis Inc, 2010)
Chlorhexidine is a type of antiseptic belonging to biguanidic group and it is large, used in dentistry, human, and veterinary medicine because it is active against Gram-positive and Gram-negative microorganisms. It can be incorporated in several types of preparations and for this reason are necessary effective analytical procedures for quality control and pharmacodynamic and pharmacokinetic studies. Chlorhexidine can be analyzed by many types of assays, however the HPLC is the most used method. In this review, various methods to analyze chlorhexidine including spectrometry, chromatography, colorimetric reaction, solid phase extraction, and capillary electrophoresis are presented and the application of these methods for the determination of chlorhexidine in biological fluids and formulations are discussed.
Keywords: review; chlorhexidine; methods of analysis